2020
DOI: 10.1172/jci124566
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte-derived microvesicles induce arterial spasms in JAK2V617F myeloproliferative neoplasm

Abstract: 8 Inserm UMS 28, Phénotypage du petit animal, Plateforme d'expérimentations coeur-muscle-vaisseaux (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 59 publications
1
50
0
1
Order By: Relevance
“…While most of the published studies have focused on mutant blood cells (eg, leukocytes, 33,63,64 red blood cells 65,66 ), two reports highlighted the pro‐adhesive phenotype of JAK2V617F mutant ECs using induced pluripotent stem cell lines from a MPN patient 62 or an endothelial‐specific JAK2V617F‐positive murine model 67 . However, no cardiovascular functional analysis was performed in these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…While most of the published studies have focused on mutant blood cells (eg, leukocytes, 33,63,64 red blood cells 65,66 ), two reports highlighted the pro‐adhesive phenotype of JAK2V617F mutant ECs using induced pluripotent stem cell lines from a MPN patient 62 or an endothelial‐specific JAK2V617F‐positive murine model 67 . However, no cardiovascular functional analysis was performed in these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…RBCEVs impact on NO bioavailability depends on several factors including the abundance of particles entering the microcirculation and their proximity to the endothelium. In vitro and in vivo studies have shown that RBCEVs by enhancing ROS production disturb NO homeostasis leading to endothelial dysfunction [ 110 , 111 , 112 ]. RBCEVs from JAK2 V617F myeloproliferative neoplasms increase endothelial oxidative stress leading to NO pathway inhibition [ 111 ].…”
Section: Biological Roles Of Rbcevsmentioning
confidence: 99%
“…Dysfunction of the endothelium is associated with the appearance and progression of the most severe human diseases, including sepsis, diabetes, stroke, dementia, and cancer [5][6][7][8][9][10]. Although these diseases are characterized by specific alterations of the endothelium, some of which have yet to be fully elucidated, inflammation has been defined as a core pathological mechanism affecting vascular beds in all these pathologies [11,12].…”
Section: Introductionmentioning
confidence: 99%